Murder in the ranks a novel - Jones, Kristi (New York, NY Crooked Lane Books, 2024)
"Algiers, North Africa, 1943. After her abusive German husband left her for dead and took their daughter with him behind enemy lines, Dottie Lincoln learned that it's better to be a trained soldier rather than a victim. As a newly minted squad leader in the Women's Army Auxiliary Corps, she spends her days moving men and materials to the front and her nights attending mandatory dances to boost the morale of the men. Despite the grueling nature of her job, she has found a sanctuary amongst the women in the Army. When Ruth, a member of her squad, is murdered, she's devastated and determined to get to the bottom of the murder. Dottie's company is the first group of American women assigned to a combat theater, and with Ruth's death, the entire operation is being questioned. Determined to do everything she can to help win the war, bring justice to her friend, and hopefully reunite with her daughter, Dottie must rise to the occasion before the killer strikes again. But when her past comes back to haunt her, Dottie must prove she's not a German spy and put a stop to a deadly conspiracy that threatens the entire American war effort."--
115304
Keywords: United States. -- Army. -- Women's Army Auxiliary Corps -- Fiction; World War -- Participation, Female -- Fiction. -- 1939-1945; Murder -- Investigation -- Fiction; Women soldiers -- United States -- Fiction; Africa, North -- Fiction; Detective and mystery fiction; Historical fiction; War fiction; Novels